Epidemiologic Characteristics of Pediatric Trauma Patients Receiving Prehospital Care in Kigali, Rwanda. Issue 9 (September 2019) - Aluisio, Adam R.; Umuhire, Olivier Félix; Mbanjumucyo, Gabin; George, Naomi; Kearney, Alexis; Karim, Naz; Nyinawankusi, Jeanne D'Arc; Uwitonze, Eric; Enumah, Sam; Scott, John W.; Mutabazi, Zeta; Ntakiyiruta, Georges; et al.
Abstract : Background: Pediatric trauma is a significant public health problem in resource-constrained settings; however, the epidemiology of injuries is poorly defined in Rwanda. This study describes the characteristics of pediatric trauma patients transported to the emergency department (ED) of the Centre Hospitalier Universitaire de Kigali by emergency medical services in Kigali, Rwanda. Methods: This cohort study was conducted at the Centre Hospitalier Universitaire de Kigali from December 2012 to February 2015. Patients 15 years or younger brought by emergency medical services for injuries to the ED were included. Prehospital and hospital-based data on demographics, injury characteristics, treatments, and outcomes were gathered. Results: Data from 119 prehospital patients were accrued, with corresponding hospital data for 64 cases. The median age was 9.5 years, with most patients being male (67.2%). Injured children were most frequently brought from a street setting (69.6%). Road traffic injuries accounted for 69.4% of all mechanisms, with more than two thirds due to pedestrians being struck. Extremity trauma was the most common region of injury (53.1%), followed by craniofacial (46.8%). The most frequent ED interventions were analgesia (66.1%) and intravenous fluids (43.6%). Half of the 16 obtained head computed tomography scans demonstrated acute pathology. Twenty-eight patients (51.9%) were admitted, with 57.1% requiring surgery and having a median in-hospital care duration of 9 days (range, 1–122 days). Conclusions: In this cohort of Rwandan pediatric trauma patients, injuries to the extremities and craniofacial regions were most common. Theses traumatic patterns were predominantly due to road traffic injury, suggesting that interventions addressing the prevention of this mechanism, and treatment of the associated injury patterns, may be beneficial in the Rwandan setting. Abstract : Supplemental digital content is available in the text.